Effects of ketone supplementation on metabolic and hormonal profiles in polycystic ovary syndrome - Sajjad Ahmed Khan; Sabah Kulsum; Anuj Subedi; Anurag Marasini; Alisha Shrestha; Tarun Pradhan; Jiba Nath Dhamala; Benju Pandit; Sadab Khan; Huma Kausar (Medicine, 2026)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder characterized by metabolic dysfunction, hyperandrogenism, and reproductive hormone imbalance. This meta-analysis aimed to evaluate the effects of ketone supplementation on anthropometric, metabolic, and hormonal parameters in patients with PCOS. Methods: A systematic search of major electronic databases was conducted to identify clinical studies evaluating the impact of ketone supplementation on BMI, serum glucose, insulin, lipid profile, and reproductive hormones in women with PCOS. Pooled analyses were performed using inverse-variance (IV) random-effects models. Heterogeneity was assessed using I 2 statistics and χ 2 tests, while publication bias was evaluated using funnel plots. Results: A significant reduction in BMI was observed following ketone supplementation (IV − 13.08; 95% CI − 17.47 to − 8.69; P < .00001; I 2 = 0%), with symmetrical funnel plots indicating low publication bias. Serum glucose levels showed a marked decrease (IV − 10.83; 95% CI − 12.98 to − 8.68; P < .00001; I 2 = 93%), and insulin levels demonstrated a similarly significant reduction (IV − 11.87; 95% CI − 15.30 to − 8.44; P < .00001; I 2 = 93%). Cholesterol levels also decreased, although the change was not statistically significant (IV − 10.77; 95% CI − 26.84 to 5.30; P = .19; I 2 = 0%). Significant reductions were identified in LH levels (IV − 5.30; P < .00001) and androgen levels (IV − 6.93; P = .0001). In contrast, FSH and estrogen levels showed significant increases (both P < .00001). Conclusion: Ketone supplementation appears to confer significant metabolic and endocrine benefits in women with PCOS, including reductions in BMI, glucose, insulin, LH, and androgens, along with increases in FSH and estrogen.